PELAPISAN TEMBAGA NIKEL PADA BAJA DAN PENGARUHNYA TERHADAP LAJU KOROSI - Syamsuir (Jurnal Konversi Energi dan Manufaktur, 2022)
The study was conducted to determine the effect of Cu-Ni coating on the corrosion rate of low carbon steel Ms 7210. The first stage of the study was Cu plating on the surface of the test sample with variations in coating holding times of 5, 10, 15, 20, and 25 minutes. The second stage is nickel plating for 10 minutes. The results showed that there was a decrease in the corrosion rate up to 0.36 mmpy when coating for 25 minutes. When compared with the raw material corrosion rate of 7.6 mmpy, the corrosion rate of steel after being coated is much lower. The longer the holding time of the coating, the thicker the layer formed, and the harder the surface that occurs, but it has an impact on decreasing the corrosion rate in the corrosive medium of 3.5% NaCl solution.